EUPHEMISMS ABOUT “ GETTING FIRED” IN ENGLISH AND UZBEK - Bakhriddinova, Dildora (Журнал иностранных языков и лингвистики, 2020)
THIS ARTICLE IS ABOUT EUPHEMISMS ABOUT “ GETTING FIRED” IN ENGLISH AND UZBEK